What got you here won't get you there: how successful people become even more successful - Goldsmith, Marshall (London Profile Books, 2013)
Goldsmith outlines twenty habits commonly found in the corporate environment and provides a systematic approach to helping you achieve a positive change in behavior.
Keywords: Success in Business